2016
DOI: 10.1074/jbc.m115.709600
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Characterization and Activity of Lymphostatin, a Multifunctional Virulence Factor of Attaching and Effacing Escherichia coli

Abstract: Attaching and effacing Escherichia coli cause diarrhea and typically produce lymphostatin (LifA), an inhibitor of mitogen-activated proliferation of lymphocytes and pro-inflammatory cytokine synthesis. A near-identical factor (Efa1) has been reported to mediate adherence of E. coli to epithelial cells. An amino-terminal region of LifA shares homology with the catalytic domain of the large clostridial toxins, which are retaining glycosyltransferases with a DXD motif involved in binding of a metal ion. Understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(58 citation statements)
references
References 65 publications
3
54
1
Order By: Relevance
“…While some of the strategies outlined here rely on direct contact between the pathogen and lymphocytes (e.g., via type III secretion), in many cases inhibition relies on diffusion of soluble proteins to meet their target cell type. Some of the factors described are active at extremely low concentrations (e.g., lymphostatin acts in the femtomolar range [16]), and the extent to which lymphocytes in circulation are affected requires study. It is evident from the ability of Shiga toxins to cause endothelial damage in kidney glomeruli that proteins produced by gastrointestinal pathogens in the gut can act distally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some of the strategies outlined here rely on direct contact between the pathogen and lymphocytes (e.g., via type III secretion), in many cases inhibition relies on diffusion of soluble proteins to meet their target cell type. Some of the factors described are active at extremely low concentrations (e.g., lymphostatin acts in the femtomolar range [16]), and the extent to which lymphocytes in circulation are affected requires study. It is evident from the ability of Shiga toxins to cause endothelial damage in kidney glomeruli that proteins produced by gastrointestinal pathogens in the gut can act distally.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphostatin (LifA, Efa-1) is one of the largest known bacterial proteins at 365 kDa and is a putative glycosyltransferase expressed by enteropathogenic Escherichia coli (EPEC) and non-O157 enterohemorrhagic E. coli (EHEC) (15). It has homology to the large clostridial toxins A and B (TcdA/B) at the N-terminal portion of the protein, where the catalytic glycosyltransferase domain of TcdA/B resides (15,16). The existence of a soluble factor capable of inhibiting mitogen-activated lymphocyte proliferation and proinflammatory cytokine expression was first described using crude bacterial lysates of the prototype EPEC strain E3248/69 (17).…”
Section: Proteins That Affect T Cell Activation and Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphostatin was first described for EPEC O127:H6 as a factor required for inhibition of mitogen-activated proliferation of human peripheral blood monocytes (PBMCs) ( 2 ), an activity that had also been observed with murine splenic and mucosal lymphocytes treated with EPEC lysates ( 3 ). Lymphostatin was recently reported to be a secreted effector of the T3SS ( 4 ); however, lymphostatin activity does not require injection of the protein into cells, as it can be demonstrated with a T3SS-negative E. coli K-12 strain bearing lifA on a cosmid ( 2 ) and detected using purified protein ( 5 ). Separately, a factor nearly identical to LifA was reported to mediate adherence of EHEC O111:H − to cultured epithelial cells (EHEC factor for adherence [Efa1]) ( 6 ), and mutations in the gene impaired type III secretion in some strains ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lymphostatin exhibits N-terminal homology with large clostridial toxins, including a conserved glycosyltransferase domain and predicted DXD catalytic motif ( 6 ). Progress in understanding the mode of action of the protein was previously hindered by the instability of plasmid clones and suspected protein toxicity; however, we recently developed an inducible system for affinity purification of LifA ( 5 ). Using site-directed mutagenesis, we observed that the DXD motif is required for lymphostatin activity and for binding of UDP- N -acetylglucosamine (UDP-GlcNAc), indicating that it may act by GlcNAc modification of cellular factors.…”
Section: Introductionmentioning
confidence: 99%